Histological profiling of gonads depicting protandrous hermaphroditism in Eleutheronema tetradactylum. Issue 6 (4th May 2017) - Shihab, I.; Gopalakrishnan, A.; Vineesh, N.; Muktha, M.; Akhilesh, K. V.; Vijayagopal, P.
Abstract : The fourfinger threadfin Eleutheronema tetradactylum is reported as a protandrous hermaphrodite from Australian waters, while being a gonochorist in reports from Singapore and India, with a single report of protandrous hermaphroditism from the latter. Histological analysis of gonads of fish from Indian waters confirms protandrous hermaphroditism in E. tetradactylum . The study was based on 480 fish examined from eight locations along the Indian coast. Mean total length ( L T ) of male fish was 240 mm with the transition to female starting from 280 mm L T . Specimens confirmed as mature females were >380 mm L T .